Persepsi Masyarakat Tani Tentang Pendidikan Anak Di Nagari Lubuk Tarok Kecamatan Lubuk Tarok Kabupaten Sijunjung - Refeldi, Refli - (Pendidikan Geografi, 2014)
The background of this study extend the life of the farmer community in the District of Lubuk Tarok Sijunjung farmers were low education and peoples income is erratic. This study aims to identify and analyze how peoples perception about the childs education farmer in District of Lubuk Tarok Sijunjung is in terms of education and income of parents. This type of research is classified into qualitative research. Here informer taken research purposive sampling and informants in this study are people who primarily work as farmers in district Lubuk Tarok Sijunjung. The results of research in the field shows that the first is based on the public perception of the farmer education once children are in priority so that their children have a higher education than the education they have ever traveled that road easier for his children to the ideals of desired children . The second is based on farmers perceptions of the educational community in terms of its income children who stated that his people have a low income due to only rely on just one source of income, but does not impede them to keep their children at school.